Edukasi Gizi terhadap Sikap Gemar Makan Sayur Kepada Anak Usia Sekolah - Retno Ayu Hapsari; Agnescia Clarissa Sera; Oriza Aditya (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2022)
Abstract – Vegetables contain vitamins, minerals, and dietary fiber. The body uses a number of vitamins and minerals from fruits and vegetables as antioxidants or as a defense against dangerous substances. By consuming enough veggies, the risk of developing unhealthy cholesterol, blood sugar, and blood pressure can be reduced. In Indonesia, fruit and vegetable consumption is still on the low side. This study sought to examine how children of school age perceived the benefits of consuming vegetables. Pre-experimental research is being done. Using the